2022
DOI: 10.52547/jad.2022.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Population status, distribution and threats of the critically endangered Gharial (Gavialis gangeticus) in Narayani River of Chitwan National Park, Nepal

Abstract: The Gharial (Gavialis gangeticus), also known as the gavial or fish-eating crocodile, is a member of the family Gavialidae, is the most threatened of the two species of crocodilians found in Nepal. However, sufficient information on its habitat characteristics influencing population status, distribution, and threats to its existence are lacking. We studied the gharial population in the Narayani River that was carried out in the winter season during December 2019 to April of 2020. During our surveys, a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The results of this study showed that gharials prefer sandy banks for basking more than other habitat or substrate types. In Nepal, previous studies have found a similar selectivity for basking on sandy banks on the Narayani River (Maskey, 1989;Maskey, Percival & Abercrombie, 1995;Thanet, 2014;Rajbhandari & Acharya, 2015) and on the Rapti River (Bhatta, 2009). On the Chambal River in India, gharials also show a preference for sandy banks (Hussain, 2009;Katdare et al, 2011;Nair et al, 2012) without regard to availability.…”
Section: Distribution Patternsmentioning
confidence: 69%
See 2 more Smart Citations
“…The results of this study showed that gharials prefer sandy banks for basking more than other habitat or substrate types. In Nepal, previous studies have found a similar selectivity for basking on sandy banks on the Narayani River (Maskey, 1989;Maskey, Percival & Abercrombie, 1995;Thanet, 2014;Rajbhandari & Acharya, 2015) and on the Rapti River (Bhatta, 2009). On the Chambal River in India, gharials also show a preference for sandy banks (Hussain, 2009;Katdare et al, 2011;Nair et al, 2012) without regard to availability.…”
Section: Distribution Patternsmentioning
confidence: 69%
“…Maskey (1989) sex ratio of 1:5 and Rajbhandari & Acharya (2015) reported a sex ratio of 1:12 in the Narayani River. A sex ratio of 1:9.5 was reported by Bhatta (2009) in the Rapti River in the CNP. The present study recorded a male to female ratio closer to 1:1 to 1:1.5 in the BNP in 2017 and 2019, respectively.…”
Section: Population Trendsmentioning
confidence: 89%
See 1 more Smart Citation
“…The direct count method showed that between 2004 and 2013, the Rapti River had a population of no more than 35 gharials (Acharya et al, 2017; Bhatta, 2009; Maskey et al, 2006). In 2016, their population increased to 82, and in 2017, it increased to 118 (Acharya et al, 2017; Poudyal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted in the Rapti River to estimate gharial population since 1980s (Acharya et al, 2017; Ballouard & Cadi, 2005; Bhatta, 2009; DNPWC, 2018; Maskey, 1989, 1998; Mishra, 2002; Poudyal et al, 2018; Rajbhandari & Acharya, 2015). To the best of our knowledge, almost all the studies on population estimation of gharials in Nepal including the Rapti River have employed the direct count method whereby the number of observed gharials in stretch of river under consideration is counted to estimate their total count (Acharya et al, 2017; Ballouard & Cadi, 2005; Bashyal et al, 2021; Bhatta, 2009; DNPWC, 2018; Maskey, 1989, 1998; Mishra, 2002; Poudyal et al, 2018; Rajbhandari & Acharya, 2015). The direct count method, however, does not account for imperfect detection (Barão‐Nóbrega et al, 2022 and references therein).…”
Section: Introductionmentioning
confidence: 99%